2011 IEEE International Conference on Services Computing 2011
DOI: 10.1109/scc.2011.72
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing DaaS Web Service Based Data Mashups

Abstract: Data Mashup is a special class of mashup application that combines information on the fly from multiple data sources to respond to transient business needs. In this paper, we propose two optimization algorithms to optimize Data Mashups. The first allows for selecting the minimum number of services required in the data mashup. The second exploits the services' constraints on inputs and outputs to filter out superfluous calls to component services in the data mashup. These two algorithms are evaluated and tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Assume also two data services: In contrast, both of S 1 and S 2 are usable for Q, to cover as much as possible of the potential values of x. Our composition algorithm extends the previous ones with: (i ) a probabilistic subsumption test to determine in a polynomial time the minimum number of services required to satisfy the value constraints that may be specified on query's parameters [6], and (ii ) a mechanism to optimize the generated composition plans based on value constraints specified in service descriptions [7].…”
Section: Service-based Query Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assume also two data services: In contrast, both of S 1 and S 2 are usable for Q, to cover as much as possible of the potential values of x. Our composition algorithm extends the previous ones with: (i ) a probabilistic subsumption test to determine in a polynomial time the minimum number of services required to satisfy the value constraints that may be specified on query's parameters [6], and (ii ) a mechanism to optimize the generated composition plans based on value constraints specified in service descriptions [7].…”
Section: Service-based Query Resolutionmentioning
confidence: 99%
“…We summarize below obtained results 5 : Composition construction and execution : Our experiments in [7] showed that our composition algorithm can handle hundreds of data services in a reasonable time. For example, for chain queries [13] and RPVs with a length of 3 or 4 object properties the algorithm was able to handle up to 400 services in less than 4 seconds.In the context of parameterized queries, our experiments in [6] showed that our algorithm to find the minimum set of services introduced only a small cost at the composition construction time (i.e., in all experiments the algorithm required less than 10% of the time needed to rewrite the query), and improved substantially the composition execution time (i.e., in all experiments the composition execution time was reduced to less than 0.75% of the time needed without optimization), as it removes redundant services. In the context of preferences queries, our experiments in [9] considered that services can be grouped in classes.…”
Section: Implementation and Evaluationmentioning
confidence: 99%
“…It is a special class of mashup application that combines information on the fly from multiple data sources. Its applications vary from addressing transient business needs in modern enterprises to conducting scientific research in e-science communities [1]. The data sources are provided through Web Services, also known as DaaS (Data-as-a-Service) or Data Service [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…An important characteristic for the enterprises of such a collaborative environment is the ability to employ data sharing with one another. By semantically annotating a DPS, it is able to be semantically discovered, mediated, and composed.Current means of development for annotations for DPSs are proposed as an afterthought to existing services [7,9,12]. One potential solution is to provide filtered data through access control.…”
mentioning
confidence: 99%
“…A domain ontology is a shared, formal description of data that is supported by computational logic for inference; resource description framework schema (RDFS) [10] and Web Ontology Language (OWL) [11] are two potential representations for ontologies on the Web. By semantically annotating a DPS, it is able to be semantically discovered, mediated, and composed.Current means of development for annotations for DPSs are proposed as an afterthought to existing services [7,9,12]. There are major issues with defining DPSs in this manner.…”
mentioning
confidence: 99%